Characteristics of halogenated flame retardants in the atmosphere of Dalian, China. (15th February 2020) - Wang, Yan; Zhang, Yuwei; Tan, Feng; Yang, Ya; Qu, Zhenping; Kvasnicka, Jacob; Chen, Jingwen
Abstract: Samples of gas and fine particulate matter (PM2.5 ) were collected in Dalian, China, a typical coastal city, to determine the concentrations, seasonal variations, influential factors, sources, and gas-PM2.5 partitioning of polybrominated diphenyl ethers (PBDEs), novel brominated flame retardants (NBFRs), and dechlorane plus (DPs) in the ambient air. Annual average concentrations of Σ7 PBDEs, BDE209, Σ6 NBFRs, and DPs were 4.40 ± 2.93, 1460 ± 2500, 7.81 ± 6.85, and 0.15 ± 0.14 pg/m 3 for the gas phase, and 2.68 ± 1.64, 4291 ± 4306, 13.6 ± 23.4, and 0.31 ± 0.22 pg/m 3 for the fine particle phase, respectively. BDE209 was the dominant congener, followed by HBB and BEH-TEBP, and seasonal variations in air concentrations were apparent for BFRs, especially those in the gas phase. Moreover, meteorological parameters and criteria air pollutants revealed significant positive correlations between temperature and less-brominated BFRs in the gas phase, and between PM2.5 and highly-brominated BFRs in the particle phase. This suggests that the presence of these compounds in ambient air may largely result from combustion-related processes. Furthermore, an analysis of the gas-PM2.5 partitioning of BFRs and DPs suggested that BFRs and DPs mostly attained equilibrium, except for some NBFRs. Due to the ban of commercial penta-, octa-, and deca-BDEs by the Stockholm Convention, emissions from historical use and combustion are becoming the important sources of PBDEs in China. Graphical abstract: Image 1 Highlights: Temperature, degradation, and combustion significantly affected air levels of BFRs. Gas-PM2.5 partitioning of BFRs and DPs suggested most of them reached equilibrium. PBDE emission from historical use or combustion still continues despite their ban.